(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
In the era of digital economy and rapid development of technologies, the introduction of innovations by banks has become the key to their survival in the financial market. The first positions in the rankings are occupied by banks that are actively implementing innovative approaches in their work. The innovation activity of banking institutions is a surprisingly dynamic process, so the domestic market of banking innovations needs constant monitoring and analysis. The study is summarizing the main trends in the introduction of innovative banking products in modern conditions of financial services market. The article considers approaches to the classification of banking innovations. The main trends of innovation implementation by commercial banks of Ukraine are generalized: remote customer service (Internet banking and mobile banking), contactless payment using contactless cards, smartphones and other NFC-devices, biometric customer identification, cooperation with fintech companies, technology virtual internet banking (neobanks), use of digital wallets and QR codes, creation of financial supermarkets. Examples of the most effective and interesting for consumers innovative solutions by banking institutions of Ukraine in recent years are given. The role of the NBU in the development of innovative financial services is considered: 1) introduction of the IBAN standard for accounts, which made international and national settlements more convenient and clear; 2) system of online verification of a person through BankID to obtain remote access to administrative, financial and commercial services; 3) creation of an experimental regulatory platform (sandbox) for testing of innovative banking services and the Expert Council on Communications with Innovative Companies. The need to obtain competitive advantages in the financial market encourages banks to constantly work on introduction of innovative banking products and technologies.